Community and personal risk factors for hepatitis C virus infection: a survey of 23 820 residents in Taiwan in 1991–2. Issue 5 (10th November 2010) - Lee, Mei-Hsuan; Yang, Hwai-I; Jen, Chin-Lan; Lu, Sheng-Nan; Yeh, Shiou-Hwei; Liu, Chun-Jen; You, San-Lin; Sun, Chien-An; Wang, Li-Yu; Chen, Wei J; Chen, Chien-Jen; ,
Abstract : Aim: The aim of this study was to explore the community-level risk factors, such as high hepatitis C viruse (HCV)-RNA positive rate and limited medical resources in a township, for HCV infection, one major cause of liver cirrhosis and hepatocellular carcinoma. Methods: This study enrolled 23 820 residents living in 155 villages of seven townships in Taiwan in 1991–2 to explore both individual and community risk factors for HCV infection. Antibodies against HCV (anti-HCV), HCV-RNA and HCV genotype in serum samples were determined by enzyme immunoassay, PCR and melting curve analysis, respectively. Results: The overall anti-HCV seroprevalence was 5.5%, HCV-RNA was detectable in 68.1% of the seropositives of anti-HCV, and genotype 1 was the most prevalent genotype (54.6%). Personal risk factors for the seropositivity of anti-HCV included older age, female gender, low educational level and history of blood transfusion. Based on the multilevel analysis, persons living in villages with high HCV-RNA-positive rates and limited healthcare resources had an increased seroprevalence of anti-HCV after adjustment for individual risk factors. The multivariate-adjusted prevalence OR (95% CI) was 3.49 (1.80 to 6.76) and 8.48 (5.07 to 14.20) for villages with medium and high HCV-RNA positive rate, respectively. The multivariate-adjusted OR (95% CI) was was 1.75 (0.76 to 4.01) and 3.91 (2.25 to 6.80), respectively, for villages with medium and poor healthcare resources. Conclusions: This study suggests that community risk factors contribute significantly to the variation in anti-HCV seroprevalence. It implies both the adequacy of healthcare resources and the treatment of patients positive for HCV-RNA may prevent individual residents from the acquisition of HCV infection from the community.